Construction of Gender-Based Islamic Inheritance Law Curriculum: Interconnection Integration Approach - Adi Nur Rohman (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2023)
The differences in the instrumentation of text and context approaches in the distribution of inheritance according to Islamic law involves the theory of gender relations as developed by contemporary thinkers. This kind of paradigm starting from the thoughts that appeared in the content of Islamic inheritance law courses in college, started from normative Islamic religious rules and then slowly began to see the cultural side that developed in society. The existence of an integration-interconnection approach is expected to link the relationship between religious dogma and science to build Islamic inheritance law that is oriented towards gender justice and adaptive knowledge in society. This article aims to elaborate a model for developing a curriculum of Islamic inheritance law in colleges that is gender justice-oriented. The study was conducted using a qualitative approach and literature study then analyzed descriptively analytically by referring to the literature related to inheritance law and gender. The results show that the integration-interconnection approach can link Islamic inheritance law and gender relations. The Islamic inheritance law curriculum development is carried out by linking normative rules with gender issues in content. Development efforts are made to find the Islamic inheritance law curriculum content gender justice-oriented in colleges.